Desvelar a cidade restinga: histórias de vida numa história urbana a contrapelo - Amorim, Adson Ney dos Santos (Universidade Federal de São Carlos, 2025)
The failed promises of progress, which set in motion a well-known history of Maceió-AL, now cloud the horizons of my interlocutors who, even so, persist in the double game of making other urban histories and, at the same time, informing the production of knowledge about the city. This work deals with the process of urbanization in Maceió, based on the paths of territorial and symbolic displacement in the lives of residents of its peripheries. These journeys, understood as products of the city and producers of it, will be the guides for understanding the state of affairs that shape Maceió's urban order. From an ethnographic perspective, based on the idea of experience and taking into account the encounters established during this research, I question the city that places me in front of an analytical mirror. By looking at the urban journeys of my interlocutors, I also reflect on my own urban condition. In methodological terms, I recover diffuse experiences from my encounters with the city and its characters, in a narrative experiment that seeks a minor urban sociology. Direct and participant observations, informal conversations and scenes from everyday life are collated with family memories, newspaper clippings and yellowed photographs, song lyrics, popular poems, stories of blessed and lost souls. Faced with a teleology of progress, which views the marginal city through the key of the absence of a modernity to be fulfilled, I argue for the need to produce an urban history against the grain, capable of facing the multiplicity of what is lived, filling the foundation of criticism with the spirit of the present and giving rise to new possible worlds.
Unveiling the restinga city: ways of life in an urban history against the grain
Keywords: História urbana; Urbanização; Conflito Urbano; Maceió; CIENCIAS HUMANAS::SOCIOLOGIA